Thermodynamic Analysis of Ozone-Safe Low Boiling Working Media for Turbo-Expander Plants - A. V. Ovsyannik; V. P. Kliuchinski (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article considers 46 low-boiling working media (LBWM) with zero potential for ozone layer destruction. Out of them, 14 ones are single-component hydrofluorocarbon refrigerants, 28 ones are multi-component mixtures of hydrofluorocarbon refrigerants, and the four ones are native refrigerants. Thermodynamic analysis of working media based on the classical turbo-expander scheme with a heat exchanger designed to cool the superheated LBWM that has left the turbo-expander has been performed. For this scheme, a cycle is constructed in T–s-coordinates. The LBWM was compared using the exergetic coefficient of efficiency (KE). In the course of the study, it was found that for some LBWM, the sequence of location of the exergetic efficiencydependences on temperature at thermodynamically optimal working medium pressures is preserved over the entire temperature range under study (from 100 to 300 оC). In other words,if the working medium has the highest exergetic efficiency coefficient, then this property is inherent in it at any temperature in a given interval. It is proposed to perform the analysis of the LBWM for exergetic efficiency at an arbitrarily selected temperature (250 оC). The study demonstrated that the highest exergetic efficiency of natural refrigerants is R600A (50.25 %), among single component hydrofluorocarbon refrigerants – R245FA (50.00 %), R1233ZD(E) (49.91 %), R236EA (49.59 %), among multi-component mixtures of hydrofluorocarbon refrigerants – R429A (47.92 %), R430A (47.49 %) and R423A (47.47 %). Out of the all examined refrigerants, the following ones have the highest exergetic efficiency of all the considered LBWM: R600A, R245FA, R1233ZD(E), R236EA, R1234ZE(Z), R236FA. They belong to both natural refrigerants (hydrocarbons) and single-component hydrofluorocarbons. It should be noted that each of these working media has its drawbacks: some have a high potential for global warming, others are explosive, and others have a high cost.